Enhancement of phytolith-occluded carbon accumulation of Moso bamboo response to temperatures elevation and different fertilization - Liu, Lijun; Chang, Scott X.; Huang, Chengpeng; Zhi, Yuyou; Jie, Yang; Yu, Xiuling; Jiang, Peikun (Frontiers in Plant Science, 2023)
The accumulation of phytolith-occluded carbon (PhytOC) in Moso bamboo could be a novel long-term carbon sequestration strategy. The objective of this study was to investigate the effects of temperature change and different fertilization on PhytOC accumulation. The pot experiment was established with different fertilization (including control (CK), nitrogen fertilizers (N), silicon fertilizers (Si), and a combination of nitrogen and silicon (NSi)) under high- and low-temperature. Despite the different fertilization, the PhytOC accumulation of the high-temperature group increases by 45.3% on average compared with the low-temperature group, suggesting higher temperature is greatly beneficial to the PhytOC accumulation. Fertilization significantly increases the accumulation of PhytOC (increased by 80.7% and 48.4% on average for the low- and high-temperature group, respectively) compared with CK. However, the N treatment increased both Moso bamboo biomass and PhytOC accumulation. The difference in the accumulation of PhytOC in Si and NSi was insignificant, indicating the combination of N and Si didn’t bring extra benefit to PhytOC accumulation compared to Si fertilizer alone. These results indicated the application of nitrogen fertilizer is a practical and effective method for enhancing long-term carbon sequestration for Moso bamboo. Based on our study, we conclude that global warming poses a positive effect on promoting the long-term carbon sequestration of Moso bamboo.